PENGARUH ATTITUDE, PERSONAL NORMS, WILLINGNESS TO PAY TERHADAP PURCHASING BEHAVIOR MAKANAN ORGANIK DI SURABAYA - Karina Farah Saraswati; Indarini Indarini; Dudi Anandya (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to understand and analyze the influence of attitude, personal norms, and willingness to pay toward purchasing behavior of organic food in Surabaya. Data processing was conducted using SPSS 18 for Windows and Amos Graphic 21 for Windows. The sampling technique that used is non-probability sampling with purposive sampling type. 150 respondents who qualify the specified characteristics of the population were the total of sample used in this research which distributed by online quetionaire.The result of this research that there was a positive influence between attitude on purchasing behavior, a positive influence between personal norms on purchasing behavior, and a positive influence between willingness to pay on purchasing behavior.